Fuel Saving Strategy in Spark Ignition Engine Using Fuzzy Logic Engine Torque Control - Triwiyatno, Aris; Sumardi, Sumardi (Makara Journal of Technology, 2012)
In the case of injection gasoline engine, or better known as spark ignition engines, an effort to improve engine performance as well as to reduce fuel consumption is a fairly complex problem. Generally, engine performance improvement efforts will lead to increase in fuel consumption. However, this problem can be solved by implementing engine torque control based on intelligent regulation such as the fuzzy logic inference system. In this study, fuzzy logic engine torque regulation is used to control the throttle position entered by the driver to achieve optimal engine torque. An engine torque vs. throttle position and engine speed mapping for vehicles with economical function is used to build this control process regulation. From the simulation result, it can be concluded that this control strategy is very effective to reduce fuel consumption and simultaneously to optimize the engine performance.